Risques naturels dans la région de l'Extrême-Nord du Cameroun et dynamique des extrêmes hydrologiques du système Chari-Logone - Frédéric Saha (Physio-Géo, 2020)
The Chari-Logone system is the main supplier of water to Lake Chad. It is also the main river draining the Far-North of Cameroon. Like other parts of the watershed, this region experienced several catastrophic floods in the three last decades. This article examines the dynamics of hydrological extremes, and therefore droughts and floods, from Logone and Chari at the stations of Bongor and N'Djamena, taking into account the context of climate change. The analyzes are based on the maximum (Qmax) and minimum (Qmin) daily flow for the period 1955-2016. XLStat and KhronoStat softwares made it possible to calculate a set of indices (irregularity index, drying coefficient, coefficient A of MYER). This software was also used to determine trends in the evolution of data over time.The flows of Logone and Chari allow to highlight successive hydro-climatic conditions in the Sahelian zone of Cameroon over the study period. The Qmax showed a break in 1971-72 at Bongor and 1972-73 at N'Djamena. This result shows the transition from wet conditions to a marked drought. In Bongor, the Qmin experienced three successive breaks, in 1971-72, 1998-99 and 2010-11. In N'Djamena, on the other hand, only one break occurred in 1982-83, with a fall in values of 55 %. From 2000, conditions became particularly contrasted, especially in Bongor, with alternating years with very different flows.On average, the coefficient A of MYER is 6.5 in Bongor and 3.2 in N'Djamena. This reflects the low power of floods. The annual value of the Qmax/Qmin ratio gradually decreased in Bongor, while it increased in N'Djamena. The drying coefficient of MAILLET is generally low (0.019/day on average); 6 months may elapse between the occurrence of Qmax and that of Qmin. Only 23 % of catastrophic floods registered in the study area occurred during wet years. This shows the important role played by other factors, such the spatial distribution of rainfall.